Clopidogrel, prasugrel, ticagrelor or vorapaxar in patients with renal impairment: do we have a winner?. (2nd December 2015) - Serebruany, Victor L.; Tomek, Ales; Pokov, Alex N.; Kim, Moo Hyun
Abstract : The optimal utilization of antiplatelet therapy in patients with renal impairment (RI) following acute coronary syndromes (ACS) represents an urgent, unmet and yet unsolved need with regards to the choice of agents, duration of treatment and potential dose/regimen adjustment. The lack of any large randomized trials designed and powered specifically in such high-risk patients, absence of the uniformed efficacy and safety data reporting policy to the FDA and endless overoptimistic publications based on post hoc analyses of primary trials sometimes exaggerating benefits and hiding risks, clouds reality. In addition, triaging RI patients is problematic due to ongoing kidney deterioration and the fact that such patients are prone to both vascular occlusions and bleeding. The authors summarize available FDA-confirmed evidence from the latest trials with approved antiplatelet agents, namely clopidogrel (CAPRIE, CURE, CREDO, CLARITY, CHARISMA); prasugrel (TRITON, TRILOGY); ticagrelor (PLATO, and PEGASUS); and vorapaxar (TRACER and TRA2P) in RI patient cohorts on top of aspirin as part of dual antiplatelet therapy (DAPT). We deliberately avoided any results unless they were verified by the FDA, with the exception of the recent PEGASUS, since Agency reviews are not yet available. Despite differences among the trials and DAPT choices, RI patients universally experience much higher (HR = 1.3–3.1) rates of primary endpoint events, and bleeding risks (HR = 1.7–3.6). However, only ticagrelor increases creatinine and uric acid levels above that of clopidogrel; has the worst incidence of serious adverse events, more adverse events, and inferior outcomes in patients with severe (eGFR <30 ml/min), especially in the lowest (eGFR <15 ml/min) RI subsets. Clopidogrel, prasugrel and vorapaxar appear safer. Moreover, less aggressive half dose (5 mg/daily) prasugrel and strict DAPT, are well justified in RI, but not predominantly triple strategies with vorapaxar as tested in TRA2P and especially in TRACER. In conclusion, data from clinical trials, their sub-studies and affiliated FDA reviews indicate that RI cause more vascular occlusions and bleeding in ACS patients treated with DAPT. Among the novel antiplatelet agents, prasugrel and vorapaxar, but probably not ticagrelor, offer advantage in RI patients.